Highly ordered columnar ITO thin film with enhanced thermoelectric and mechanical performance over wide temperature range. Issue 18 (15th September 2022) - Luo, Bingwei; Cao, Lili; Luo, Fei; Zhou, Haitao; Ma, Kexin; Liu, Dabo; Wang, Linbin; Hu, Shaoxiong; Sun, Kun; Zhang, Shulin
Abstract: Indium tin oxide (ITO) based thin films offer the possibility to improve the performance of high-temperature thermocouples by providing good sensitivity and reliability over a wide temperature range. In this study, a thin but robust ITO-based thin-film thermocouple, with a low-crystallised highly ordered columnar structure, was fabricated. The electrical conductivity exhibited a high temperature-dependent sensitivity owing to the increasing density with increasing temperature. The nano-hardness and interfacial robustness were evaluated and found to exhibit excellent service reliability at high temperatures because of the low thermal stress. Furthermore, the similar mechanical and electrical performances of the thin films, after annealing at 600 and 800 °C, demonstrated that the enhanced performance was mainly determined by the orientation of the ITO thin films. An enhanced Seebeck coefficient (∼100 μV K −1 ) was obtained for the ITO thin film after annealing at 1000 °C, resulting in a special structure with profuse nanoholes. These results highlight the good mechanical performance and stability of the thermoelectric properties of highly ordered columnar thin films over a wide temperature range, and can serve as a guide for the preparation of thin but robust functional ceramic-based materials.